Work or Service on own Account? - Stelina, Jakub (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The author analyses the problem of the nature of employment of entrepreneurs performing registered business activities. From the point of view of the types of employment provided for in Polish law the performance of self-employment by entrepreneurs should be qualiﬁed as employment of a civil law nature, because the subject of such activity can only be services, and not subordinate work. An entrepreneur is not allowed to enter into employment contracts in the course of business. On the other hand, services performed in the course of business activity may be qualiﬁed as work under the Constitution, which in Art. 24 states that work is under the protection of the state. This provision uses the concept of work in a broad sense. This means that certain constitutional standards of labor protection can, and even should, be applied to entrepreneurs, which, however, cannot lead to the equalization of their status with that of employees.